Developing teacher identity in preservice education : experiences and practices from Portugal - Flores, Maria Assunção (2014)
This chapter draws upon a wider project on the development of teacher identity in preservice education. The aim is to look at the effects of a given pedagogy which was designed and implemented in a Master degree in Teaching. The project draws upon existing international research literature on teacher identity which highlights the dynamic and multifaceted nature of the process as well as the pivotal role of preservice teacher education as a context for identity development. The main themes are explored through student teachers’ own voices (N=20). Issues such as learning about becoming a teacher: exploring the unknown; making the implicit explicit: initial beliefs and theories about being a teacher; teachers’ role and work: from a student perspective towards a teacher perspective; expectations about teaching as a profession: scepticism and hope; and aspirations as preservice teachers will be analyzed. The chapter concludes with some conclusions and recommendations for others who might like to try this pedagogy in their respective teacher education milieus.